THE INFLUENCE OF CUSTOMER EXPERIENCE AND BRAND TRUST ON PURCHASING DECISIONS (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
This study aims to analyze the influence of customer experience and brand trust on purchasing decisions for Muslim fashion products in South Sumatra. Utilizing a quantitative approach with explanatory research design, data were collected from 225 respondents through questionnaires and analyzed using Structural Equation Modeling-Partial Least Square (SEM-PLS). The results indicate that customer experience has a positive and significant influence on purchasing decisions. Similarly, brand trust is proven to have a positive and significant impact on consumer purchasing decisions. Furthermore, the analysis reveals that customer experience and brand trust simultaneously exert a positive and significant effect on purchasing decisions, explaining 74.8% of the variance. These findings suggest that positive shopping experiences and high levels of brand trust are critical factors for consumers in the competitive Muslim fashion market. Practically, this research provides recommendations for fashion businesses in South Sumatra to enhance customer experience through service optimization and to strengthen brand trust through product quality and consistency to drive sales and foster long-term customer loyalty.